Experimental investigation on composite panels of cold-formed steel and timber. (15th November 2021) - Kyvelou, Pinelopi; Reynolds, Thomas P.S.; Beckett, Christopher T.S.; Huang, Yuner
Highlights: Experimental investigation on cold-formed steel and timber board composite panel was performed. Mechanical properties, connector behaviour and flexural strength of the composite panel were obtained. Structural benefits due to the composite action between the two materials were quantified. Existing design rules to predict moment capacity and flexural stiffness were assessed. Abstract: Timber panels and cold-formed steel sheeting are widely used in the construction industry, especially in prefabricated structures, temporary housing and informal settlements. This is because these materials are widely available, can be cut and fixed with hand tools, and their lightweight makes them easy to transport and build with. When used together, there is a potential for composite action developing between the timber panels and the underlying steel sheeting, which is currently ignored in design. A composite panel of oriented strand boards and cold-formed steel sheeting is proposed herein and its overall structural behaviour is experimentally investigated. Based on results obtained from material, push-out and flexural tests, its mechanical properties are determined and the predominant failure modes are highlighted. The feasibility of mobilising composite action between the components of the proposed system is proven and the derived benefits, both in terms of load carrying capacity and stiffness, are quantified. It is demonstrated that harnessing the beneficial influence of composite action can lead to substantial improvements of the overall structural performance of the proposed composite panel, offering the potential to improve significantly the quality of housing in informal developments and rapidly urbanising areas.